DAMPAK PENGGUNAAN GADGET TERHADAP PERKEMBANGAN PSIKOLOGI PADA ANAK SEKOLAH DASAR - Fifin Dwi Purwaningtyas; Yesi Septiana; Hesti Aprilia; Galuh Candra (PSIKOWIPA (Psikologi Wijaya Putra), 2023)
Technology use has a beneficial and negative impact on children's growth and development. Users will become addicted to their devices if they are used constantly. The negative effects are especially concerning because they are so widespread among children who use electronic devices. Therefore, it is crucial for parents to provide, monitor, and limit their children's access to electronic devices. This research aims to ascertain how technology affects the mental growth of primary school students. This research is qualitative in nature, employing procedures like organized interviews. The findings of this study suggest that children's emotional development may be negatively affected by their excessive use of electronic devices.